PENGARUH CITRA MEREK DAN HARGA TERHADAP MINAT PEMBELIAN ULANG SARI ROTI - Mabaroh, Naila Alva; Mukhroji, Mukhroji (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
This study aims to determine the effect of brand image and price on repurchase interest in Sari Roti. The sample used in this study were consumers who had bought bread cider at least twice or more, totaling 96 respondents. The data analysis technique used in this study to determine all variable influences was validity test, reliability test, t test, F test, multiple regression linear with SPSS tools. The results of this study are the variable Brand image (X1) has a positive and significant effect on the interest in repurchasing bread cider with a significant value of 0.018 <0.05 and the variable Price (X2) has no significant effect on the interest in repurchasing bread cider with a significant value of 0.101> 0.05.